Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1111/j.1558-5646.2010.01101.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Patterns Shape Introgression Dynamics and Species Succession Within the European White Oak Species Complex

Abstract: The reproductive system of hybrids is an important factor shaping introgression dynamics within species complexes. We combined paternity and parentage analyses with previous species characterization by genetic assignment, to directly identify reproductive events that occurred within a stand comprising four European white oak species. Comparing species status of parent pairs provided a precise quantification of hybridization rate, backcrosses, and intraspecific matings in two life stages. The detailed mating sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
120
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(128 citation statements)
references
References 78 publications
(107 reference statements)
6
120
2
Order By: Relevance
“…On the contrary, we observed that relatively young individuals start to produce acorns. Also, our results did not support an increased selffertilisation rate, as our estimate of the contemporary selfing rate equalled 2%, which is comparable with other findings for European white oaks in the main species range (Streiff et al 1999;Curtu et al 2009; Burczyk 2010; Lepais and Gerber 2011). It seems that the study population produced enough pollen to maintain cross-pollination, and/or some pre-or post-zygotic mechanisms (Buschbom et al 2011) prevent more intense inbreeding.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…On the contrary, we observed that relatively young individuals start to produce acorns. Also, our results did not support an increased selffertilisation rate, as our estimate of the contemporary selfing rate equalled 2%, which is comparable with other findings for European white oaks in the main species range (Streiff et al 1999;Curtu et al 2009; Burczyk 2010; Lepais and Gerber 2011). It seems that the study population produced enough pollen to maintain cross-pollination, and/or some pre-or post-zygotic mechanisms (Buschbom et al 2011) prevent more intense inbreeding.…”
Section: Discussionsupporting
confidence: 79%
“…In European white oaks effective pollen dispersal is usually bimodal, as a result of limited pollen dispersal within a population and a large pollen immigration from outside (e.g. Streiff et al 1999;Salvini et al 2009;Chybicki and Burczyk 2010;Buschbom et al 2011;Lepais and Gerber 2011). However, due to very low effective pollen immigration (as our results suggest), in the study population a distribution of mating distances can be unimodal with a peak at short distances.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations